Milosc i przetrwanie : uzdrawiajaca moc intymnosci w swietle nauki - Ornish, Dean.; Smagacz, Henryk (Warszawa : Jacek Santorski & Co., 1998)
Polish translation of "Love and Survival". A study of how love and intimacy can affect one's health and longevity of life.
Includes bibliographical references (p. [253]-269).
Keywords: Coronary heart disease -- Psychological aspects; Love; Intimacy (Psychology); Longevity; Health